Analisis Implementasi Total Quality Management (TQM) dalam Pelayanan Instalasi Gawat Darurat - Rahmi, Irma Kurnia; Sastrawan, Sastrawan; Khalik, Lalu Abdul (Universitas Malahayati, 2026)
ABSTRACT This study aims to analyze the implementation of Total Quality Management (TQM) in the Emergency Department (ED) of RSUD Nusa Tenggara Barat Provincial Hospital. A qualitative case study design was employed to explore how TQM principles are applied in the context of hospital service quality, particularly in high-pressure and dynamic emergency care settings. Analyzing the implementation of Total Quality Management (TQM) in the Emergency Installation services of the Regional General Hospital of West Nusa Tenggara Province. Data were collected through in-depth interviews, participant observation, and document review. Thematic analysis was conducted based onDonabedian’s model (structure, process, outcome) and key TQM principles such as continuous improvement, staff involvement, and data-driven management. Findings indicate that TQM implementation in the ED is not yet fullyoptimized. Major challenges include limited human resources, inadequate physical infrastructure, and an underdeveloped information system. However, several TQM elements have been partially adopted, including routine staff training, improved communication, and increased staff participation. These efforts have contributed positivelyto patient perceptions, particularly in terms of response time and staff professionalism. The implementation of TQM has contributed to improvements in ED service quality. Nonetheless, further systemic strategies are needed tostrengthen operational systems, integrate data management via SIMRS, enhance staff capacity, and foster a participatory quality culture. A comprehensive and sustainable approach is essential to fully internalize TQM principles across all service areas. Keyword: Total Quality Management, Emergency Department, Service Quality, Hospital, Thematic Approach. ABSTRAK Penelitian ini tujuannya menganalisis implementasi Total Quality Management (TQM) dalam pelayanan Instalasi Gawat Darurat (IGD) RSUD Provinsi Nusa Tenggara Barat. Pendekatan kualitatif dengan desain studi kasus digunakan untuk menjelajahi sejauh mana prinsip-prinsip TQM diterapkan dalam konteks peningkatan mutu layanan rumah sakit, khususnya pada unit dengan karakteristik dinamis dan tekanan tinggi seperti IGD. Menganalisis implementasi Total Quality Management (TQM) dalam pelayanan Instalasi Gawat Darurat Rumah Sakit Umum Daerah Provinsi Nusa Tenggara Barat. Data diperoleh melewati wawancara mendalam, observasi partisipatif, dan telaah dokumen.Analisis dilakukan menggunakan pendekatan tematik dengan mengacu pada model Donabedian (struktur, proses,hasil), serta prinsip-prinsip utama TQM seperti perbaikan berkelanjutan, keterlibatan staf, dan manajemen berbasis data. Temuan menunjukkan bahwa implementasi TQM di IGD belum berjalan secara optimal. Hambatan utamameliputi keterbatasan sumber daya manusia, infrastruktur fisik yang belum memadai, serta sistem informasi yangbelum sepenuhnya terintegrasi. Meskipun demikian, beberapa prinsip TQM mulai diterapkan, antara lain pelatihanrutin, penguatan komunikasi, dan partisipasi staf. Praktik ini berdampak positif terhadap persepsi pasien, terutama dalam hal kecepatan respons dan profesionalisme tenaga medis. Penerapan TQM memberikan kontribusi terhadap peningkatan mutu layanan IGD. Namun, dibutuhkan strategi penguatan sistem, integrasi data berbasis SIMRS, pengembangan kapasitas sumber daya manusia, serta pembentukan budaya mutu yang partisipatif. Pendekatan yang sistemik dan berkelanjutan diperlukan agar prinsip TQM dapat terinternalisasi secara menyeluruh di seluruh lini layanan. Kata Kunci: Total Quality Management, Instalasi Gawat Darurat, Mutu Layanan, Rumah Sakit, Pendekatan Tematik.